Analisis Pengaruh Tata Kelola Perusahaan dan Karakteristik Perusahaan terhadap Pemilihan Auditor pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Androni Susanto (Faculty of Economics, Universitas Internasional Batam, 2021)
This study aimed to test the relative effect of corporate governance and firm characteristics in making client auditor choice in companies listed in the Indonesia Stock Exchange (IDX). Variables used in this study are independence of board of directors, board size, audit committee size, institutional ownership, foreign ownership, sponsor ownership, government ownership, ownership concentration, firm complexity, industry classification, firm risk, company size, leverage, and profitability. Samples from this study using the companies listed on the Indonesia Stock Exchange and were selected using purposive sampling method. The data used in this study are the financial statements of each company published (www.idx.co.id). The data have been obtained will be tested with binary logistic regression. Program of Statistical Product and Service Solutions (SPSS) were used in this study research. The results of this study indicate that the board size, audit committee size, institutional ownership, foreign ownership, ownership concentration, firm complexity, industry classification, company size, and profitability has positive significant impact on auditor choice. On the other hand, this study indicate that independence of board of directors and firm risk has negative significant impact on auditor choice. The other variables in this study like sponsor ownership, government ownership, and leverage has no significant impact on auditor choice.